Detection of behavior in electronic games - a systematic mapping - Luccas, Matheus dos Santos; Pereira, Leonardo Tortoro; Castelo Branco, Kalinka (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2025)
Introduction: Behavior detection in electronic games enables adaptive experiences, yet lacks comprehensive analysis of techniques for constructivist serious games. Objective: To systematically map behavior detection technologies, analyzing their purposes, efficiency, and adaptability for educational contexts. Methodology: Systematic mapping using Parsifal, evaluating technologies, implementation challenges, and effectiveness metrics across 39 selected studies. Results: Machine learning, statistical methods, and ensemble approaches dominate, applied for dynamic difficulty and emotion detection. Key challenges include data requirements and visualization tool limitations.